2003
DOI: 10.5254/1.3547777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chain Length of Amine and Nature and Loading of Clay on Styrene-Butadiene Rubber-Clay Nanocomposites

Abstract: Polymer nanocomposite is one of the highly discussed research topics in recent time. In this paper, we have reported the preparation and the properties of different nanoclays based on sodium montmorillonite, bentonite and potassium montmorillonite and organic amines of varying chain lengths, and Styrene Butadiene Rubber (SBR)-clay nanocomposites. The clays and the rubber nanocomposites have been characterized with the help of Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
70
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 0 publications
6
70
0
Order By: Relevance
“…[1][2][3] Development of novel fillers such as carbon nanotubes, 4,5 nanoclay, 6,7 graphene, 8,9 silica, 10,11 and diamond 12 nanoparticles has led to increased interest in polymer reinforcement. The effect of fillers on the mechanical response is very strain dependent.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Development of novel fillers such as carbon nanotubes, 4,5 nanoclay, 6,7 graphene, 8,9 silica, 10,11 and diamond 12 nanoparticles has led to increased interest in polymer reinforcement. The effect of fillers on the mechanical response is very strain dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Quite a number of publications exist in the field of SBR/clay nanocomposites and these are briefly summarized below. SBR/clay nanocomposites have been prepared by the solutionblending technique by Ganter et al [12] and Sadhu and Bhowmick [13][14][15]. SBR latex/clay nanocomposites were prepared by Zhang et al [16], Wang et al [17,18], and Wu et al [19] by acid coagulation of the mixture formed by mixing SBR latex and clay/water dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also reported that, when one considers a straight-chain organo-amine, the best result is achieved with octadecyl amine (ODA). 29 Thus, in this study, we used ODA as the organic intercalate.…”
Section: Introductionmentioning
confidence: 99%